6 Breaking bad news training: lessons from outside healthcare. (13th October 2019) - Soosaipillai, Gehan; Archer, Stephanie; Bielinska, Anna-Maria; Ashrafian, Hutan; Darzi, Ara
Abstract : Healthcare workers frequently break bad news, but often lack formal training. Other job sectors (e.g. military and human resources) also break bad news on a regular basis. Lessons from these sectors may be valuable when developing training resources within healthcare. Aim: To understand how those who work outside of healthcare are trained to break bad news. Method: Using a snowball approach, a convenience sample of 20 participants from a range of sectors were invited to participate. Twelve completed semi-structured interviews (see table 1 ). Audio recordings were transcribed, anonymised and subjected to thematic analysis. Results: Though formal training was lacking in many sectors, the military, in particular, provided rigorous and consistent training courses for their Notification and Visiting Officers. Experiential learning by observing others or through own practice, or interactive learning in a safe and simulated environment (e.g. role-play) was common. Some sectors recognised the challenge of breaking bad news and have installed supportive measures. Digital learning was seen as 'the way forward', with accessibility and flexibility that matches modern working styles. There was a demand for more learning on breaking bad news, even in a digital medium, but there was little recognition of such resources being available. Conclusion: Other job sectors apply similar learning modalities to healthcare but place greater emphasis on training their workforce in breaking bad news. There is a need for research studying enhanced training for breaking bad news in healthcare by focusing on preparedness and support as this would likely offer comparable benefits for the healthcare sector.